Problem Based Learning to Improve Creative Thinking Skills and Technological Literacy on Virus Material - Zelvia Aprima Putri; Dewi Insyasiska; Poncojari Wahyono (JURNAL EKSAKTA PENDIDIKAN (JEP), 2023)
Creative thinking skills and technological literacy are important skills possessed by students in the 21st century. However, many students are still poorly trained these skills, so they need learning strategy that can improve them. This classroom action research aims to improve creative thinking skills and technological literacy through the application of PBL. The method used is Stephen Kemmis and Robyn McTaggart (2007) model, includes planning, acting, observing and reflecting stages in each cycle. The research subjects were 34 students of class X-10 State Senior High School 1 Batu. The results obtained in the form of the average value of creative thinking skills in the precycle of 55.37%, cycle I of 73.97%, while in cycle II of 84.19%, while the average score of technological literacy in the precycle of 66.43, cycle I of 75.62, while in cycle II of 87.68. This shows that the application of PBL can improve creative thinking skills and technological literacy in students of Class X-10 State Senior High School 1 Batu. The implication of this research is that the application of PBL develops problem solving skills, creative thinking in formulating solutions, and being able to utilize the role of technology appropriately so that students can continue to adapt in the digital era.